2011
DOI: 10.2176/nmc.51.490
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Intraoperative Computed Tomography in Surgery for Low-Grade Gliomas: a Comparative Study Between Two Series Without and With Intraoperative Computed Tomography

Abstract: We have routinely used an intraoperative CT (i-CT) system in over 800 neurosurgical procedures since 1997. To investigate the utility of i-CT in low-grade glioma (LGG) surgery, we investigated whether i-CT improved the extent of tumor resection and prognosis in 46 patients with histologically confirmed LGG consisting of 27 patients with World Health Organization grade II astrocytoma, 12 with oligodendroglioma, and 7 with oligoastrocytoma. The patients were divided into two groups, 23 who underwent tumor resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…1C, D). Hosoda et al3) reported that surgical resection with intraoperative CT prolongs survival by acquiring more complete surgical resection, which was confirmed during or immediately after the procedure.…”
Section: Discussionmentioning
confidence: 93%
“…1C, D). Hosoda et al3) reported that surgical resection with intraoperative CT prolongs survival by acquiring more complete surgical resection, which was confirmed during or immediately after the procedure.…”
Section: Discussionmentioning
confidence: 93%
“…Yes, depending on the sequence 22 Yes 20 Yes, although orientation is limited owing to the different planes 23,24 2D/3D 3D 3D 2D, 3D with specialized transducers or a stacked 2D volume 23 Need for contrast agent Not necessary; discrimination between two types of tissue can be improved with the use of contrast agent and it gives the opportunity to acquire real-time vascular-phase images 22,25 Not necessary; discrimination between two types of tissue can be improved 26 Not necessary; discrimination between two types of tissue can be improved and real-time vascular-phase images acquired 27,28 Cost (machine and facility) €€€ 22 24,27 . Delay is dependent on operator (maximum a few minutes) 23…”
Section: Anatomical Informationmentioning
confidence: 99%
“…Yes, highly interfering. Positionwise may even be impossible 22 Yes, depending on the modality and the possibility of a sliding gantry on a railtrack 24,26 Not in general and presents no logistical challenges 23 . Yes, it needs direct contact with specimen 4,21…”
Section: Interference With Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to use the intraoperative CT data to align it to the preoperative CT or MRI dataset. This is typically not the preferred method for brain tumor surgery due to the disadvantages of exposure to ionizing radiation, and poor soft tissue delineation, but some groups have explored its use [55,88]. Haberland et al [76] also used iCT in combination with iUS.…”
Section: Intraoperative Ctmentioning
confidence: 99%